Q. 2 D5.0( 1 Vote )

# Factorize the following expressions:

1 – 36x^{2}

Answer :

= 1 – 36x

^{2}

Given equation can be simplified as,

= (1)^{2} – (6x)^{2}

It is of the form (p)^{2} – (q)^{2}Where p = 1 and q = 6x

∴ using the identity: (p)^{2} – (q)^{2} = (p + q)(p – q)

We get,

⇒ (1)^{2} – (6x)^{2} = (1 + 6x)(1 – 6x)

1 – 36x^{2} = (1 + 6x)(1 – 6x)

Rate this question :

Factorize the following expressions:

16x + 64x^{2}y

Factorize the following expressions:

2a^{3} – 3a^{2}b + 2a^{2}c

If (2x + 1) and (x – 3) are the factors of ax^{2} – 5x + c, then the values of a and c are respectively

If one of the factors of x^{2} – 6x – 16 is (x + 2) then other factor is

Factorize the following expressions:

xy – xz + ay – az

Factorize the following expressions:

10x^{3} – 25x^{4}y

Factorize the following expressions:

a^{3} + 125

Factorize the following expressions:

8x^{3} – 27y^{3}

Factorize the following expressions:

p^{2} + q^{2} + r^{2} + 2pq + 2qr + 2rp

Factorize the following expressions:

1 – 36x^{2}